Evaluación geológica-minera del Prospecto La Valenciana, Macizo del Deseado, Provincia de Santa Cruz, Argentina - Méndez, Carolina Carmen (2006)
The Valenciana prospect is a silver, gold, and base-metal deposit located in the province of Santa Cruz in the north central portion of Macizo del Deseado. The area is about 480 km2. The veins are composed of quartz with crustiform – coloform banding and occur within 200 to 400m in depth. They were emplaced in Jurassic volcanic and volcaniclastic rocks. The age of the ore deposit is estimated to be about 153 Ma. The Valenciana vein is the most important orebody of this prospect; it is hosted in a N-S to NNE-strikink fault that dips 75º to the west and extends for 2 km along strike. The geologic map at a scale of 1:50,000 was created from studies of LandSat-TM color composite images and with GPS in the field. The geochemistry, petrography, and mapping information studies were compiled into a GIS. The geochemical studies of the volcanic rocks suggest that the prospect is associated with a volcanic arc zone situated in an extensional environment. According to the ore mineralogy and alteration, the vein is classified as an epithermal deposit of low sulfidation.